Dopplervelocimetria nas gestações complicadas por hiperglicemia: curva do índice de pulsatilidade da artéria umbilical - Llanos, Isabel Cristina Franco Salem [UNESP] (2013)
To construct a curve PI umbilical exclusive of pregnancies complicated by diabetes mellitus (DM) or hyperglycemia and compare it with reference curves (Arduini and Rizzo, 1990; Sakamoto, 2007). A longitudinal study where 163 women were included and excluded cases of multiple births, malformations, technical difficulty and less than five prenatal visits. We assessed maternal age, body mass index (BMI) before pregnancy, number of pregnancies and is associated with smoking and hypertension (HA), and levels of glycated hemoglobin (HbA1c) in late pregnancy. In total, 431 measurements were evaluated umbilical PI, between 24 and 41 weeks gestation. For each gestational week were performed measures of central tendency and dispersion values assigned and calculated indices of the respective percentiles (P5, 10, 25, 50 and 95). The correlation equation prediction and confidence intervals (95% CI) were estimated by linear regression analysis. We carried out a qualitative comparison of the three curves overlap and quantitative study between the curves and Sakamoto (2007). The adopted threshold of significance of 95% (p <0.05).The prediction equation was expressed by umbilical PI [PI umb = 1.521 - 0.018 * week of pregnancy]. The limits of the P95 evolved umbilical PI always below the limits of the reference curve of Arduini ...